International clinical recommendations on scar management. - Mustoe, T; Cooter, R; Gold, M; Hobbs, F; Ramelet, A; Shakespeare, P; Stella, M; Téot, L; Wood, F; Ziegler, U (2002)
Many techniques for management of hypertrophic scars and keloids have been proven through extensive use, but few have been supported by prospective studies with adequate control groups. Several new therapies showed good results in small-scale trials, but these have not been repeated in larger trials with long-term follow-up. This article reports a qualitative overview of the available clinical literature by an international panel of experts using standard methods of appraisal. The article provides evidence-based recommendations on prevention and treatment of abnormal scarring and, where studies are insufficient, consensus on best practice. The recommendations focus on the management of hypertrophic scars and keloids, and are internationally applicable in a range of clinical situations. These recommendations support a move to a more evidence-based approach in scar management. This approach highlights a primary role for silicone gel sheeting and intralesional corticosteroids in the management of a wide variety of abnormal scars. The authors concluded that these are the only treatments for which sufficient evidence exists to make evidence-based recommendations. A number of other therapies that are in common use have achieved acceptance by the authors as standard practice. However, it is highly desirable that many standard practices and new emerging therapies undergo large-scale studies with long-term follow-up before being recommended conclusively as alternative therapies for scar management.